1999
DOI: 10.1038/sj.jidsp.5640217
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of the Hair Follicle: A Short Journey into terra incognita

Abstract: This paper delineates briefly why the immunology of the hair follicle matters (e.g., anti-infection defense, hair growth control by immunomodulatory agents, sequestration of follicular autoantigens), and which open key questions await clarification. We then focus on the murine hair follicle immune system (HIS) and its immune privilege. We show how the murine HIS is gradually constructed during hair follicle morphogenesis, and how it is transformed during hair follicle cycling. Key characteristics of the HIS ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 12 publications
3
102
0
1
Order By: Relevance
“…However, follicle-derived HSC activity may be of particular relevance to the human condition. It is now well established that rodent hair follicles display immune privilege, and our work and that of others has indicated that this is true for human dermal sheath cells (Paus et al, 1999;Reynolds et al, 1999); such cells may therefore prove to be admirable donor cell types in stem-cell-based therapies. Further, the ability to readily access dermal cell populations by skin biopsy, rather than a potentially more invasive procedure required for other stem cell types may make them particularly appropriate as a source of autologous or allogeneic HSC activity.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, follicle-derived HSC activity may be of particular relevance to the human condition. It is now well established that rodent hair follicles display immune privilege, and our work and that of others has indicated that this is true for human dermal sheath cells (Paus et al, 1999;Reynolds et al, 1999); such cells may therefore prove to be admirable donor cell types in stem-cell-based therapies. Further, the ability to readily access dermal cell populations by skin biopsy, rather than a potentially more invasive procedure required for other stem cell types may make them particularly appropriate as a source of autologous or allogeneic HSC activity.…”
Section: Discussionmentioning
confidence: 65%
“…There is growing interest in hair follicle immunology and evidence that the follicle has a unique immunological profile (Paus et al, 1999;Gilliam et al, 1998;Westgate et al, 1991). Therefore, it is possible to envisage that the capacity to produce haematopoietic cells locally in skin could play a role in, for example, wound healing and immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MHCI and MHCII molecules (and other immune system genes) are downregulated in normal human anagen (growing) hair follicles, and because of this, portions of the hair follicle are considered an anatomic compartment with immune privilege (IP; refs. [36][37][38][39]. In the setting of autoimmune or inflammatory diseases associated with hair loss, there is felt to be a loss of IP as evidenced by increases in the expression of MHCI and MHCII molecules as well as other immunoregulatory proteins (40).…”
Section: Discussionmentioning
confidence: 99%
“…The head and neck carcinoma cell lines (886LN and SQCC/Y1) were kindly provided by Dr. Dong Shin (Winship Cancer Institute) and were maintained in DMEM:F12 (1:1) supplemented with L-glutamine (1 mmol/L) and 10% FBS at 37 C and 5% CO 2 atmosphere. Primary human keratinocytes (PHK) were purchased (LifeLine Technologies) and grown in complete defined media as recommended by the supplier and maintained at 37 C and 5% CO 2 atmosphere. PHKs were used between passages 3 and 6.…”
Section: Cellsmentioning
confidence: 99%
“…In the same region, the few Langerhans cells that are detectable are functionally impaired in their antigen-presenting capacity since they do not express MHC class II (56). Also, potent immunosuppressants such as TGF-β1 and α-melanocyte-stimulating hormone (α-MSH) are prominently expressed in the proximal anagen hair follicle (2,57).…”
Section: Immune Privilege Collapsementioning
confidence: 99%